Morpho-metaphony and so-called “marginal” vowel system in the northern Salentino dialects (Atti del Sodalizio Glottologico Milanese, 2025)
The northern Salentino vowel system, provided with five stressed vowels, is nowadays conceived as an original Sicilian system, later influenced by the Neapolitan one. Indeed, each of the two mid vowels shows two different metaphonic outcomes (/ɛ‒MET/ ~ /i+MET, jɛ+MET/; /ɔ‒MET/ ~ /u+MET, wɛ+MET/), by producing a underlying phonological heptavocalic system. I argue that such a vowel configuration is irregular from a diachronic phonetic development, rather depending as a whole on the rise of morphological patterns. The difference between intra- and inter-paradigmatic morphological schemas can be responsible for the major preservation of the Sicilian vowel system in the 1st class femm. adjectives and nouns, if compared with its rare retention in the 3rd class nouns and 2nd class adjectives.